Global burden trends of tension-type headache, 1990–2021: socio-demographic patterns, age-period-cohort effects, and frontier analysis from the GBD 2021 study - Wang, Can; Liao, Chao; Liu, Yuyin; Chen, Peng; Xie, Yuanlun; Tian, Li (Frontiers in Neurology, 2025)
BackgroundTension-type headache (TTH) is one of the most prevalent neurological disorders globally. While previous studies have examined TTH epidemiology across different regions, few have comprehensively analyzed how socio-demographic factors influence its patterns and trends. This study aimed to analyze TTH burden trends from 1990 to 2021 and their relationship with socio-demographic development.MethodsData on prevalence, incidence, and years lived with disability (YLDs) for TTH were extracted from the Global Burden of Disease study (GBD) 2021, covering global, 5 SDI regions, 21 regions, and 204 countries. We used absolute numbers and age-standardized rates from 1990 to 2021. Spearman correlation assessed the relationship between rates and the Socio-Demographic Index (SDI). An age-period-cohort model disentangled temporal effects across different SDI levels, while frontier analysis evaluated improvement potential relative to SDI.ResultsDespite modest decreases in age-standardized rates (prevalence: −0.56%, incidence: −0.32%, YLDs: −2.27%), absolute TTH cases reached 2.01 billion in 2021, increasing 56.4% from 1990. TTH burden showed moderate positive correlations with SDI, with High SDI regions having highest rates. Contrasting trends emerged: globally and in High and High-middle SDI regions rates decreased, while Middle SDI regions showed significant increases (prevalence: +5.83%). APC analysis revealed global peak prevalence at age 32.5 years, with period effects showing decreases in High SDI regions but increases in Middle SDI regions. Cohort effects indicated decreasing risks in recent High/High-middle SDI cohorts but increasing risks in Middle SDI regions.ConclusionOur research reveals that TTH remains a substantial global health challenge, with its burden increasingly shifting toward younger populations in middle-income countries. This epidemiological transition, coupled with significant untapped potential for burden reduction even in high-SDI nations, demands the urgent development of context-specific public health strategies to mitigate the growing impact of this highly prevalent disorder.